2021
DOI: 10.5194/acp-2021-611
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulated impacts of vertical distributions of black carbon aerosol on meteorology and PM<sub>2.5</sub> concentrations in Beijing during severe haze events

Abstract: Abstract. Vertical profiles of black carbon (BC) play a critical role in BC-meteorology interaction which influences PM2.5 (particulate matter with a diameter of 2.5 μm or less) concentrations. In this study, we used the Weather Research and Forecasting with Chemistry model (WRF-Chem) coupled with an improved integrated process (IPR) analysis scheme to investigate the direct radiative effect (DRE) of BC with different vertical profiles on meteorology and PM2.5 concentrations in Beijing during two severe haze e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Chen et al. (2022), by using the WRF‐Chem model, found that the different vertical profiles of BC always caused the largest warming in the lower troposphere instead of at the surface, because higher altitudes would have smaller BC concentration and lower altitudes would have weaker solar radiation for absorption. Wang et al.…”
Section: Simulated Changes In Meteorological Fields By Aerosol Drementioning
confidence: 99%
“…Chen et al. (2022), by using the WRF‐Chem model, found that the different vertical profiles of BC always caused the largest warming in the lower troposphere instead of at the surface, because higher altitudes would have smaller BC concentration and lower altitudes would have weaker solar radiation for absorption. Wang et al.…”
Section: Simulated Changes In Meteorological Fields By Aerosol Drementioning
confidence: 99%